2011
DOI: 10.4081/jear.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Using parasitoid wasps in Integrated Pest Management in museums against biscuit beetle (Stegobium paniceum) and webbing clothes moth (Tineola bisselliella)

Abstract: -Biscuit beetle (Stegobium paniceum) and webbing clothes moth (Tineola bisselliella) cause much damage to museum objects. Some objects and materials are very attractive to these two pest species and objects are often re-infested after treatment. For some years parasitoid wasps have been used in biological pest control to treat and reduce infestations of stored product pests in food processing facilities. Their application in museums is still new and in a research stage. Results from five different museums in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
(3 reference statements)
0
6
0
1
Order By: Relevance
“…Two parasitic wasps, Lariophagus distinguendus Forster and Theocolax elegans Westwood, which are natural enemies of S. paniceum, are attracted to volatiles of stored cereal grains which represent the preferred substrates of their hosts. 16,22,50 Therefore volatile compounds identified from CMPMs that could be attractive to both S. paniceum and S. paniceum parasitoids deserve further research. This information could provide a theoretical framework for establishing a biocontrol system, based on CMPM volatiles, in which parasitoids are used to control S. paniceum infesting CMPMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two parasitic wasps, Lariophagus distinguendus Forster and Theocolax elegans Westwood, which are natural enemies of S. paniceum, are attracted to volatiles of stored cereal grains which represent the preferred substrates of their hosts. 16,22,50 Therefore volatile compounds identified from CMPMs that could be attractive to both S. paniceum and S. paniceum parasitoids deserve further research. This information could provide a theoretical framework for establishing a biocontrol system, based on CMPM volatiles, in which parasitoids are used to control S. paniceum infesting CMPMs.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed that semiochemical volatiles participate directly in the interactions between S. paniceum and host CMPMs. Two parasitic wasps, Lariophagus distinguendus Forster and Theocolax elegans Westwood, which are natural enemies of S. paniceum , are attracted to volatiles of stored cereal grains which represent the preferred substrates of their hosts 16,22,50 . Therefore volatile compounds identified from CMPMs that could be attractive to both S. paniceum and S. paniceum parasitoids deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…Low oxygen atmosphere is achieved using Nitrogen, Argon or anoxia treatments with oxygen scavengers in small bags. Still quite new and under development is the biological method application using parasitoid wasps, for example, against biscuit beetles, webbing clothes moths, or furniture beetles [ 43 , 44 , 45 , 46 , 47 , 48 ]. First, results show that it is working if the location of the infestation is known and parasitoid wasps are commercially available (this is not the case for all pests, but just a small selection).…”
Section: Introductionmentioning
confidence: 99%
“…IPM in museums uses different chemical-free options to treat infestation, such as freezing (Florian, 1990;Strang, 1997), controlled heat treatment (Strang, 1992;Pinniger, 2003), anoxia (Gilberg, 1989(Gilberg, , 1991Maekawa & Elert, 2003), parasitoid release (Querner & Biebl, 2011), or insect growth regulators (Gilberg & Roach, 1997) (see also Querner and Kjerulff (2013) for an overview of treatment methods used in museums). But we clearly show that the often discussed 'housekeeping' or 'deep clean' is an important part of preventive conservation, to reduce moth activity in museums and stores.…”
Section: Control Of Infestationmentioning
confidence: 99%